The frailty phenotype as a predictor of all-cause mortality in community-living individuals aged 65 years and older: The Tromsø Study 2001-2015. - Langholz, Petja Lyn (UiT Norges arktiske universitet, 2017)
Background: In the light of an aging population, risk factors for adverse outcomes in the elderly constitute an important field of research. Frailty is an age-related syndrome of increased vulnerability to stressors due to declines in several physiologic systems. The aim of this study was to assess the prevalence of frailty and to investigate its ability to predict all- cause mortality in a Norwegian population. Methods: This prospective cohort study used baseline data from 736 men and women aged 65 years and older in the fifth Tromsø Study (2001-02) to assess the prevalence of frailty, which was defined by a modified version of the frailty phenotype proposed by Fried and colleagues. Participants were followed for all-cause mortality until 31st December 2015. Cox regression models, stratified by sex, were used to analyse the association between frailty and mortality with adjustment for several potential confounders. Results: The prevalence of frailty and pre-frailty was 3.7% (n=27) and 37.6% (n=277), respectively. With increasing frailty level, individuals displayed a higher prevalence of diseases and disability and were more likely to be older, female and less educated. Multivariate-adjusted hazard ratios indicated an increased risk of mortality in frail men (HR 7.10 (95% CI 3.04,16.61)) and frail women (HR 2.95 (95% CI 1.39,6.26)) compared to non- frail elderly. Pre-frailty showed an overall weaker association with mortality, which was only statistically significant in men. Conclusion: The frailty prevalence in this Norwegian study sample was lower than previously reported for other countries. Frailty was highly associated with mortality and the findings suggest that the risk might be higher for frail men than frail women.